THE IMPORTANCE OF FOREIGN EXPERIENCES IN THE SUSTAINABLE DEVELOPMENT OF UZBEKISTAN ON THE BASIS OF A GREEN ECONOMY - Khudayorov Azizbek Avaz ugli (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstact: The article analyzes the experiences of foreign countries, such as the USA, China, South Korea, France, Japan, and Great Britain, in achieving sustainable development based on a green economy in a period of increasing global environmental problems, and studies the priority areas of their use in the conditions of Uzbekistan. Scientifically based proposals and recommendations are presented for the reorganization, formation, and development of the Uzbek economy from the point of view of environmental requirements.